Teacher in K.H. Ahmad Dahlan's Perspective; A Study of Historical Reflection - Syahrul Syahrul; Didin Saefuddin; E. Bahruddin; Adian Husaini; Arif Budi Raharjo (Edumaspul: Jurnal Pendidikan, 2023)
Teachers became pioneers of change and awakened the intelligence of the native people in the public sphere in the early 20th century. The journey of the nation cannot be separated from the significant role of K.H. Ahmad Dahlan as a figure in Indonesian Islamic education. He established alternative education and prepared militant teacher cadres. This research aims to uncover K.H. Ahmad Dahlan's response to Dutch colonial education with the cadres of his teachers and his conception of the figure of a teacher. This study employs a qualitative approach with data sources from relevant literature such as books, journals, and newspapers or magazines, with a historical-philosophical approach and content analysis. The findings reveal that K.H. Ahmad responded to the need for teachers with a high spirit of struggle. This led him to establish Al-Qismul Arqa (Madrasah Mu’allimin). In K.H. Ahmad Dahlan's perspective, a teacher is a dedicated educator, progressive, and a good role model in the process of educating, teaching, guiding, and inspiring students to become individuals with noble character, devoted to Allah, possessing critical thinking skills, self-confidence, proficient in religious knowledge, broad-minded, and with a strong determination to serve Muhammadiyah, especially, and the Muslim community and society at large. They are ready to be arrows that disseminate the ideas of Islamic renewal amidst society.